(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To review the clinical characteristics, paraclinical features, treatment outcomes of Fournier’s gangrene, and some factors related to the mortality rate of Fournier’s gangrene patients at 115 People’s Hospital from 2018 to 2023. Methods: Retrospective case series study: patients diagnosed with Fournier’s gangrene and treated at 115 People’s Hospital from January 2018 to May 2023. Results: There were 30 patients (21 males and 09 females) diagnosed with FG and treated. The average age was 60.23 ± 14.34 (31 - 87 years old), mainly in the 40 - 70 age group. Skin infections accounted for the highest proportion at 43.3%, followed by gastrointestinal infections at 16.7%, and urogenital infections at 6.7%. Most patients had symptoms of perineal pain (100%), perineal swelling (66.7%), subcutaneous emphysema (46.7%), urinary retention (20%). FG on the basis of genitourinary diseases was the most common (56.6%). Pathogenic bacteria isolated under microbiological conditions at the hospital were predominantly anaerobic, with E. coli, Klebsiella and Proteus spp being the most common strains (21.9%). Active treatment included internal medicine (resuscitation, broad-spectrum antibiotics, nutrition, wound care, etc.) and surgery (surgical debridement of necrotic tissue, fecal and urinary diversion). The mortality rate of the study was 23.3%. Multiple organ failure and septic shock were the main contributing factors to death. Female gender, diabetes, high severity index, and extensive spread of FG lesions significantly influenced the mortality rate. Conclusion: FG is a rare, rapidly progressing disease with a high mortality rate. Early treatment including resuscitation, antibiotic therapy, and prompt surgical debridement is as soon as possible.